Linguistic Aspects of [Ninna-Nanna di Madonna] Part of the Calabrian Dialect Poem la Notte di Natale by Fr. Vincenzo Padula (1819-1893) - Artur Katolo (The Francis de Sales Scientific Society (TNFS.PL), 2022)
The aim of this article is to present a language analysis of one of the most beautiful dialectal poem of Fr. V. Padula. The dialect used by Fr. V. Padula is to be called the Acrian dialect (spoken in the city of Acri, Cosenza Province), which belongs to the group of northern Calabrian dialects. The lullaby [Ninna-nanna di Madonna], sung by Holy Mary, is the second part of the poem La Notte di Natale. No one ever was capable as Fr. V. Padula, to carry the Acrian dialect a such high summits of lyricism and piety. The Acrian dialect served him to know and testify the Calabrian society and culture. [Ninna-nanna di Madonna] includes in itself some biblical references to the main truths of the faith of Christianity.